HUBUNGAN GAYA KOMUNIKASI PIMPINAN DAN PEGAWAI DENGAN KINERJA PEGAWAI - Yuwarti, Harti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
Communication is a basic context for the human to human to know one another. In an agency or company requireda good cooperation between management and employees in order to achieve an organizations goals are good.The method used was a survey, using a quantitative approach, using test analysis correlation data to obtain thevalue of the relationship and was followed by a statement in the form of questionnaires distributed to the selectedrespondents using sampling techniques as much as 31 respondents.Populasi dalam penelitian ini adalah sebesar33 orang dan sampel yang digunakan dalam penelitian ini adalah 31 orang. Based on the research that has beendone, it can be seen that there is a very strong relationship between the two variables, and the correlation valueof the relationship between the leadership style of communication - with the employee for 0814, this show is apositive relationship going. It means that the better the communication style of leadership - employees are interwovenwith the employee, the performance is also better. Value of 0.814 for the relationship if interpreted in theinterpretation of the correlation coefficient table is in the interval from 0.80 to 1.000,Is at a very strong level.